(untitled) (Diametros, 2005)
The internal realism proposed by Hilary Putnam caused much discussion in the philosophical community. Some considered how to classify this view; is it still realism or just ordinary idealism? Others, however, tried to judge it quite benevolently, as something intermediate in the classical realism-idealism opposition. In the article we share the latter opinion, though with some reservations. We maintain that unless an “ontological” foundation is provided for the thesis of conceptual relativity, Putnam’s view has to be treated as a form of linguistic idealism rather than an intermediate road. The reinterpretation that we have carried out seems to be supported by the natural realism that Putnam presently holds. The crucial issue is that of worldmaking; does language independently determine the way in which cognized reality is articulated, or is another material factor involved, one that is independent of language, such as the human body, for example? On the other hand, if internal realism is to mean that we can step outside the limits of language itself, then the additional assumption of the existence of an independent material factor in the constitution of the world leads to a paradox.